Antioxidant and Antilipid Peroxidation Potential of Supercritical Fluid Extract and Ethanol Extract of Leaves of Vitex Negundo Linn. - Nagarsekar, K. S. (Medknow Publications & Media Pvt Ltd, 2011)
Supercritical fluid extract and ethanol extract of Vitex negundo Linn. were subjected to the chromatographic evaluation for identification of their constituents. Free radical scavenging activity of both extracts was studied by subjecting them to DPPH assay. IC(50) values of ethanol and supercritical fluid extract of Vitex negundo indicate that ethanol extract has stronger reducing potential and ability to scavenge free radicals as compared to the supercritical fluid extract. The in vivo effect of extracts on lipid peroxidation was studied using ethanol induced oxidative stress model in rat. Ingestion of extracts for 14 days exhibited significant reduction in plasma MDA level of stressed animals. Ethanol extract exhibited higher in vivo antilipid peroxidation potential as compared to supercritical fluid extract which correlated well with radical scavenging potential of extract.